Indonesian Islamic Studies: Selected Dissertation Bibliography 2000-2016 - Saputro, M. Endy (DINIKA : Academic Journal of Islamic Studies, 2016)
The shifting of religious authority has been a primary issue of (un)published dissertations on Indonesian Islam. The collapse of Soeharto regime, more or less, takes salient effect on the rise of new religious authorities; while on the same time it provokes social change in the society. New religious mass organizations, such as Hizbut Tahrir Indonesia, Front Pembela Islam and Front Umat Islam, seem to be main critical discussion in certain dissertation in line with some topics which problematizes prominent Islamic organizations, Muhammadiyah and Nahdlatul Ulama, under new framework of analysis. New media and Islamic banking have to be other domain authorities that carefully discussed in some dissertation. Put it in another topics, gender issue take a untrivial position. In short, these dissertations topics tend to discuss more on Islam in popular authorities.Keywords:Islamic Studies, Bibliography, Dissertation, Indonesia